Versatile derivatives of carbohydrate-binding modules for imaging of complex carbohydrates approaching the molecular level of resolution. (October 2006) - Ding, Shi-You; Xu, Qi; Ali, Mursheda K.; Baker, John O.; Bayer, Edward A.; Barak, Yoav; Lamed, Raphael; Sugiyama, Junji; Rumbles, Garry; Himmel, Michael E.
The innate binding specificity of different carbohydrate-binding modules (CBMs) offers a versatile approach for mapping the chemistry and structure of surfaces that contain complex carbohydrates. We have employed the distinct recognition properties of a double His-tagged recombinant CBM tagged with semiconductor quantum dots for direct imaging of crystalline cellulose at the molecular level of resolution, using transmission and scanning transmission electron microscopy. In addition, three different types of CBMs from families 3, 6, and 20 that exhibit different carbohydrate specificities were each fused with either green fluorescent protein (GFP) or red fluorescent protein (RFP) and employed for double-labeling fluorescence microscopy studies of primary cell walls and various mixtures of complex carbohydrate target molecules. CBM probes can be used for characterizing both native complex carbohydrates and engineered biomaterials.